Mycobacteriosis in Atlantic salmon farmed in British Columbia - Brocklebank, John (2003)
Mycobacterium chelonae was identified as the cause of incidental mortality in Atlantic salmon smolts following introduction to seacages. Source of infection was not confirmed. Polymerase chain reaction was a useful method of detecting and speciating the genus Mycobacterium in infected stocks. Clinical management and public health implications of infection are discussed.